Peculiarities of improving the process of making managerial decisions in the activities of (state) general educational institutions of the city of Moscow - Shafiullina A. A. (Modern education development: theory, techniques and practice, 2018)
this article analyzes the key problems of management – managerial decision making with emphasis on activities of educational institutions (public), the geographic scope of the study – Moscow.
Keywords: управленческие решения; уровни образования; государственные общеобразовательные учреждения; managerial decisions; state educational institution; educational institutions in the city of Moscow